Embryological and cytochemical features of Scilla autumnalis L. - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2010)
Nucellar epidermal cells in the micropylar region of Scilla autumnalis L. differentiate into a nucellar cap. It secretes a PAS-positive exudate filling the micropyle. A group of cells at the chalazal end of the nucellus forms a hypostase. Close to the antipodals, the hypostase cells contain abundant starch grains, suggesting a function as a storage tissue. Another ovular structure is the obturator. It secretes an exudate that stains deeply with PAS reaction, and it takes a role in directing the growth of pollen tubes toward the micropyle. Cytochemical tests in the mature embryo sac indicate the presence of high amounts of proteins, polysaccharides, and lipids in the cytoplasm of the egg, synergids, antipodals, and central cell, appearing to be the site of intensive synthetic activity. The presence of a PAS-positive wall completely surrounding the egg cell and synergids is an unusual feature worthy of mention. Antipodals undergo polytenisation to reach ploidy levels of up to 128n. Another embryological feature of S. autumnalis is the development of an Onagrad type of embryo and a helobial type of endosperm.
Keywords: Scilla autumnalis; embryo; endosperm; antipodals; cytochemistry; ORNITHOGALUM-CAUDATUM LILIACEAE; EMBRYO SAC; WINTERACEAE